A Stable and Conductive Covalent Organic Framework with Isolated Active Sites for Highly Selective Electroreduction of Carbon Dioxide to Acetate. (8th July 2022) - Qiu, Xiao‐Feng; Huang, Jia‐Run; Yu, Can; Zhao, Zhen‐Hua; Zhu, Hao‐Lin; Ke, Zhuofeng; Liao, Pei‐Qin; Chen, Xiao‐Ming
Abstract: Electroreduction of CO2 to acetate provides a promising strategy to reduce CO2 emissions and store renewable energy, but acetate is usually a by‐product. Here, we show a stable and conductive two‐dimensional phthalocyanine‐based covalent‐organic framework (COF) as an electrocatalyst for reduction of CO2 to acetate with a single‐product Faradaic efficiency (FE) of 90.3(2)% at −0.8 V (vs. RHE) and a current density of 12.5 mA cm −2 in 0.1 M KHCO3 solution. No obvious degradation was observed over 80 hours of continuous operation. Combined with the comparison of the properties of other catalysts with isolated metal active sites, theoretical calculations and in situ infrared spectroscopy revealed that the isolated copper‐phthalocyanine active site with high electron density is conducive to the key step of C−C coupling of *CH3 with CO2 to produce acetate, and can avoid the coupling of *CO with *CO or *CHO to produce ethylene and ethanol. Abstract : Compared to multiple active sites, an isolated active site with high electron density may be more suitable for electroreduction of CO2 towards the C2 product acetate, and can avoid the coupling of *CO with *CO or *CHO to produce ethylene and ethanol.